Etiological agents of community-acquired pneumonia in adult patients in Turkey; a multicentric, cross-sectional study - Koksal, Iftihar; Ozlu, Tevfik; Bayraktar, Ozlem; Yilmaz, Gurdal; Bulbul, Yilmaz; Oztuna, Funda; Grubu, Tucap Calisma (Turkish Assoc Tuberculosis & Thorax, 2010)
This cross-sectional study was intended to investigate the etiology of community-acquired pneumonia (CAP) in adult patients receiving no prior antibiotic therapy. Etiological agents were identified in 137 (62.8%) of 218 patients, the most frequent being Streptococcus pneumoniae (14.7%), Mycoplasma pneumoniae (13.8%) and respiratory syncytial virus (10.1%). A single pathogen was detected in 50.9% of cases and mixed pathogens in 11.9%. Typical pathogens were determined in 35.8% of cases, atypical pathogens in 20.2% and viral pathogens in 20.6%. Chronic obstructive pulmonary disease was a common (42.7%) comorbidity. S. pneumoniae was the most common pathogen in adult patients with CAP. Atypical pathogens were more common in patients < 65 years old, M. pneumoniae being the most common in this age group. Our results suggest that initial empiric antibiotic treatment in patients with CAP should cover S. pneumoniae and M. pneumoniae in Turkey.
Keywords: Community-acquired pneumonia; risk factors; etiology of pneumonia